Functional roles for evolutionarily conserved Spt4p at centromeres and heterochromatin in Saccharomyces cerevisiae - Crotti, Luciana B (Nature Publishing Group, 2004)
The kinetochore (centromeric DNA and associated proteins) mediates the attachment of chromosomes to the mitotic spindle apparatus and is required for faithful chromosome transmission. We established that evolutionarily conserved Saccharomyces cerevisiae SPT4, previously identified in genetic screens for defects in chromosome transmission fidelity (ctf), encodes a new structural component of specialized chromatin at kinetochores and heterochromatic loci, with roles in kinetochore function and gene silencing. Using chromatin immunoprecipitation assays (ChIP), we determined that kinetochore proteins Ndc10p, Cac1p, and Hir1p are required for the association of Spt4p to centromeric (CEN) loci. Absence of functional Spt4p leads to altered chromatin structure at the CEN DNA and mislocalization of the mammalian CENP-A homolog Cse4p to noncentromeric loci. Spt4p associates with telomeres (TEL) and HMRa loci in a Sir3p-dependent manner and is required for transcriptional gene silencing. We show that a human homolog of SPT4 (HsSPT4) complements Scspt4-silencing defects and associates with ScCEN DNA in an Ndc10p-dependent manner. Our results highlight the evolutionary conservation of pathways required for genome stability in yeast and humans.